The Teaching Learning Activity in Mathematics for Youth and Adult Education - de Souza Medrado, Jackelyne; Nardi, Roberto [UNESP]; da Silva Dias, Marisa [UNESP] (FapUNIFESP (SciELO), 2021)
The aim of this article is to present the results of a doctoral research developed through a formative practice carried out in the Supervised Curricular Internship (SCI) discipline with undergraduates of a Licenciate Mathematics course in the context of Youth and Adult Education (YAE). The research question was based on the question: What theoretical-practical learning, from the initial training of Mathematics teachers, developed at SCI, contribute to the constitution of being a teacher for YAE? The Historical-Cultural Perspective and Activity Theory were considered the theoretical references for the research. The constitution of the empirical data occurred through an open questionnaire, participant observation, field diary, productions of the participants throughout the development of the internship, and audio-video recordings of the interventions, conductors, and moments of reflections on these actions. With the analysis of the data, guided by the dialectical movement from the rise of the abstract to the concrete in the interrelationship between singular-particular-universal, of historical-dialectical materialism, there is a movement of appropriation of the Mathematics teaching activity in YAE, with highlights in the changes between motives, senses, and meanings in the formative process of being a teacher for this teaching modality.
A Atividade de Aprendizagem da Docência em Matemática para a Educação de Jovens e Adultos
Keywords: Activity theory; Historical-dialectical materialism; Supervised internship; Teacher education